Android-Based Maritime English Application to Support the Learning of Nautical Cadets At Maritime Department - Aprizawati; Bobi Satria; Zusniati (International ABEC, 2022)
The purpose of this research is to create a basic application of Maritime English that is useful in supporting learning and improving the skills of Maritime English cadets at Maritime Department especially for nautical program. Maritime English is one of the English language learning with a special purpose that is indispensable in communicating, maintaining safety and activities at sea both nationally and especially internationally. The research problem is many seafarers do not understand maritime terms, either in their daily conversations at sea, from ship to ship or ship to shore station, whether it's about health, safety, or security issues in the shipping industry. In this millennial era, it is very rare for sailors to read books to increase their knowledge because they tend to be boring and unpleasant. Therefore, as a basic step in the maritime department, researchers created an android-based application consisting of vocabulary and pictures about maritime English to increase interest in learning Maritime English. There are lots of English apps but not much about sailing. Therefore, with the proliferation of android-based gadgets, as the result, the researcher was successful find an application as a solution to support students or cadets as a basic learning in Maritime English.